Railroading religion : Mormons, tourists, and the corporate spirit of the West - Walker, David, 1975- (University of North Carolina Press, 2019)
"Walker tracks how 'knowledge' about Mormon life was generated among settlers, railroad agents, travelers, boosters, and bureaucrats from Sacramento to Salt Lake to Washington D.C. and stops between. How ordinary Americans articulated and advanced their own theories about Mormondom, Walker argues, accomplished nothing less than the rise of religion as a category of both the popular and scholarly imagination. As it happened, the burgeoning of railroad-related alliances and businesses stimulated LDS Church officials to mobilize in ways that ironically yielded increasingly dynamic and expansive religious institutions. Rather than eradicating or diminishing Mormonism western railroads and their boosters helped to establish it as a normative American religion"--